Development of foreign language capability as a valued human resource asset within the military : a thesis presented in partial fulfilment of the requirements for Master of Business Studies in Human Resource Management at Massey University, Palmerston North - Smith, Fiona (Massey University, 2012)
English has held the status as a global language for many years, and has been the language in which the corporate and military sectors conduct their international operations. However, due to globalisation, technological advances and challenging economic times, the environments in which businesses and defence forces operate have evolved considerably. Defence forces are increasingly involved in nontraditional operations, in non-traditional geographical locations, working alongside non-traditional international security partners. In light of the changing role and expectations of the military, Conway (2005) suggests that the military sector has been guilty for too long of assuming that English, the traditional language of international diplomacy, politics, economics and military operations, will remain the prevalent language. While the corporate sector has recognised foreign language capability as a human resource asset, its importance and operational relevance is largely unacknowledged within the military sector. The aim of this study was to examine how modern English speaking defence forces, such as the New Zealand Defence Force (NZDF), are addressing the issue of „linguistic complacency‟ (Crystal, 2003), and what plans are in place to develop human resources as foreign language capable assets. For the NZDF, the concept is new. Consequently, a preliminary investigation into one of the single Services, the Royal New Zealand Navy (RNZN), was undertaken. It identified Mandarin Chinese, French, Hindi and Japanese as the foreign languages of greatest applicability to the Service. Census survey results of RNZN uniformed personnel indicated that over half of respondents had some second-language ability (of varying proficiency level) across more than forty languages. Despite the reported foreign language capacity, the results, when compared with the Service‟s desired skills sets, suggested that there are a number of gaps between the ideal and current capability requirements. A United States Department of Defense model for developing foreign-language capability was discussed as a blueprint for how the RNZN and NZDF could look to bridge these gaps through the strengthening of educational ties with defence partners.
Keywords: New Zealand Defence Force; Personnel management; Foreign language capability; Bilingualism; Foreign language skills; Human resource assets